2022
DOI: 10.1158/1538-7445.am2022-4075
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4075: Meta-analysis of neuroblastoma single cell RNA-seq datasets identifies conserved and divergent gene expression programs across human and preclinical models

Abstract: Neuroblastoma is a highly heterogeneous disease not only in the clinical presentation of individual patients, but also in the cellular composition of any given tumor. Insights into this diversity have only recently been enabled due to advancements in single cell technologies, which have facilitated investigation of this disease at unprecedented resolution and detail. Coinciding with the growing number of scRNA-seq technologies, so too are the number of single cell datasets encompassing neuroblastoma patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, other neuroblastoma singlecell studies have raised the question of whether MES cells are bona fide malignant cells. Indeed, a variety of non-malignant cells (Schwann cells, SCPs, fibroblasts, myofibroblasts) that express mesenchymal genes are present in neuroblastoma tumors, making it difficult to discern bona fide MES neuroblastoma cells from non-malignant cells expressing similar gene expression programs 81 . In our analysis, we separated MES and ADRN malignant cells and showed that both populations had the same inferred copy number variation.…”
Section: Malignant Cells In Neuroblastoma Retain Features Of Sympatho...mentioning
confidence: 99%
“…However, other neuroblastoma singlecell studies have raised the question of whether MES cells are bona fide malignant cells. Indeed, a variety of non-malignant cells (Schwann cells, SCPs, fibroblasts, myofibroblasts) that express mesenchymal genes are present in neuroblastoma tumors, making it difficult to discern bona fide MES neuroblastoma cells from non-malignant cells expressing similar gene expression programs 81 . In our analysis, we separated MES and ADRN malignant cells and showed that both populations had the same inferred copy number variation.…”
Section: Malignant Cells In Neuroblastoma Retain Features Of Sympatho...mentioning
confidence: 99%